Der «vacirende Gott». Arthur Schnitzlers Reflexionen auf die eigenen Schaffens(un)möglichkeiten: [The «Unemployed God». Arthur Schnitzler’s Reflexions on his own Creative (In)Capabilities] (Studia austriaca, 2018)
This article deals with Arthur Schnitzler’s early sketch Er wartet auf den vazierenden Gott (1886) (He is Waiting for the Unemployed God), which reveals Schnitzler’s poetological reflections on his own writing. Not unlike a «vazierender Gott», he too had to wait for moments of inspiration, even in later years. This attitude helps to explain Schnitzler’s doubts about his own capability to finalise his literary sketches and his uncertainty about his status as a «real» author. The «vazierende Gott» thus becomes an important metaphor for any discussion of the problems of Schnitzler’s literary production.